Políticas públicas, participação e emancipação : narrativas das mulheres da Comunidade Quilombola de Lagoa Grande, zona rural de Feira de Santana - Bahia - Morais, Adrielly Ferreira (2024)
Understanding the state as the main party responsible for promoting social welfare, this work transposes the merely technical approach to public policies, highlighting participatory democracy as a vital factor for equality. Despite the fact that the domination of patriarchy is more evident in rural areas, the emancipatory process of women in rural areas has been observed in recent years, based on a movement of change that reflects the growing role of women in the economy and in social and political representation. Therefore, this study sought to analyze the experience of women from the Quilombola Community of Lagoa Grande, in the rural area of Feira de Santana - BA, with public policies and their possible links with women's emancipation in the countryside in order to answer the following question: What is the impact of public policies on the structures of inequality and the strengthening of women's emancipation in the Quilombo of Lagoa Grande? In this process, pertinent strategies were adopted to achieve the proposed objective, which initially comprises the theoretical approach basing the conceptual and methodological perspectives, as methodological tools for data collection are used conversation circles, oral reports and a recording documented on video, a problem tree is also presented that imagistically represents the problems discussed throughout the proposed dialogues. The field research presents results that confirm the significant participation of women in the community, making it possible to get an idea of the reality of the women of Lagoa Grande with regard to the public actions of the state and their perception of female emancipation in the countryside. The data obtained in this research shows a favorable scenario for female participation in the community in various areas, as well as identifying demands that depend on public actions that are appropriate to a given reality